PREVALENCE OF HELMINTH INFECTIONS AMONG PRIMARY SCHOOL CHILDREN IN GUSAU LOCAL GOVERNMENT AREA, ZAMFARA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
This study aimed to examine the prevalence of helminth infections in primary school children in Gusau Local Government Area of Zamfara State. Stool samples were collected from 245 pupils and analyzed using the Kato-Katz technique. A total of 130 (53.1%) were positive for helminth infections with Hookworms having the highest rate of prevalence at 56.2%. Stool samples of pupils in primary 1 to 5 were randomly selected and the results show that there was a high prevalence rate in Primary 1 pupils (73.3%) while Primary 3 pupils had the least (34.2%). The prevalence of helminth infections was higher among males (59.3%) than females (47%) (p = 0.000). Overall helminth infections were higher in the 5–7 year age group (59.2%) than in the other age groups (p= 0.064) Hookworm and Hymenolepis eggs co-infection (3%) was the most common mixed infection and were significantly higher in males than females. The total prevalence rate (53.1%) in this study was above the stipulated range (12.5–50.2% for soil-transmitted helminthiases), as reported by the Nigerian Federal Ministry of Health. Holistic control measures must be enforced by the Zamfara State Government to reduce the prevalence rate of helminth infections among school children within the state.
Keywords: Children; Gusau; Helminth Infections; Primary School